RECURSOS TECNOLÓGICOS EN EL APRENDIZAJE SIGNIFICATIVO DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES INFORMÁTICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO OCTUBRE 2023-MARZO 2024 - CARRIEL ZAMBRANO NAYELY ALEJANDRA (2024)
The present research topic on "Technological resources in the meaningful learning of students of the Pedagogy of Experimental Sciences Computer Science career, with the general objective of determining the effectiveness of the use of technological resources in the meaningful learning of students of the degree in pedagogy of experimental computer sciences at the Technical University of Babahoyo, academic period October 2023-March 2024", having as a reference that it is important to guarantee that the implementation of technological resources within the classroom has a positive influence on the improvement of meaningful student learning. That is to say, technological resources are fundamental since they are now an essential part of the teaching-learning process, which contributes to the progress of education in the future, the design and type of research that was used, descriptive, explanatory, and documentary, and The approach was mixed, for a population of 470 students corresponding to all semesters of the Pedagogy of Experimental Sciences in Computer Science, the data collection technique was applied such as the survey, used as the questionnaire composed of 10 questions about technological resources. used in meaningful learning within the Likert scale. The results obtained allowed us to know that there is a positive influence on the significant learning of students through the use of technological resources, concluding that students recognize that the use of technological resources has a positive impact on their significant learning, however, only It manifests itself when the appropriate and responsible use of these resources is made since it can be a powerful tool to improve education.